Penerapan Materi Ajar PAI Dan Budi Pekerti Dalam Meningkatkan Kemampuan Kognitif Anak Berkebutuhan Khusus Di Sekolah Luar Biasa B, C, D, G Al-Mashduqi Garut - Salamudin, Ceceng; Nurlatifah, Saadah (STAI Al-Musaddadiyah Garut, 2024)
This research is motivated by the cognitive abilities of children with special needs at Al-Mashduqi Special School (SLB) for categories B, C, D, and G in Garut. The categories of special needs at Al-Mashduqi SLB include B (hearing impaired), C (intellectually disabled), D (physically disabled), and G (multiple disabilities). Observational findings indicate that children with special needs exhibit varying cognitive abilities in line with their specific challenges. The objectives of this study are: to describe the cognitive abilities of children with special needs at Al-Mashduqi SLB; to explore the application of Islamic Religious Education (PAI) and moral education material for these children; and to examine how these educational materials enhance the cognitive abilities of children with special needs at Al-Mashduqi SLB. The research employs a qualitative descriptive method. Data sources are both primary and secondary. Primary data include information from informants, observations of the learning process, and other written materials. Secondary sources consist of books and other materials directly related to the research. Data collection techniques include observations, interviews, and documentation. Data analysis involves three stages: data reduction, data presentation, and conclusion drawing. The validity and reliability of the data are ensured through triangulation techniques involving observations, interviews, and documentation. The results of this study indicate that the application of Islamic Religious Education (PAI) and moral education material has effectively enhanced the cognitive abilities of children with special needs in categories B, C, D, and G at Al-Mashduqi SLB. These enhancements reach levels C1, C2, and C3, as measured through formative tests. The delivery of PAI and moral education materials has made students more active and enabled them to achieve learning objectives and outcomes effectively, meeting the Minimum Mastery Criteria (KKM). Keywords : PAI and Moral Education Material, Cognitive Abilities, Children with Special Needs B, C, D, G.